Dialogue for Interreligious Understanding Strategies for the Transformation of Culture-Shaping Institutions - Swidler, Leonard; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
This invaluable volume gathers together the cumulative insight of more than fifty years of Leonard Swidler's work on dialogue. The founder and president of the Dialogue Institute, Swidler offers through experience and research his theory and tools of interreligious, intercultural, and international dialogue.
Keywords: Religions; Ecumenical movement; Comparative Religion; Ecumenical Studies